The search for new efficient inhibitors of SARS-COV-2 through the De novo drug design developed by artificial intelligence - da Fonseca, Aluísio Marques; Cabongo, Sadrack Queque; Caluaco, Bernardino Joaquim; Colares, Regilany Paulo; Fernandes, Carla Freire Celedonio; dos Santos, Hélcio Silva; de Lima-Neto, Pedro; Marinho, Emmanuel Silva (Journal of biomolecular structure & dynamics, 2023)
The pandemic caused by Sars-CoV-2 is a viral infection that has generated one of the most significant health problems worldwide. Previous studies report the main protease (Mpro) as a potential target for this virus, as it is considered a crucial enzyme in mediating replication and viral transcription. This work presented the construction of new bioactive compounds for possible inhibition. The De novo molecular design of drugs method in the incremental construction of a ligant model within a receptor model was used, producing new structures with the help of artificial intelligence. The research algorithm and the scoring function responsible for predicting orientation and affinity in the molecular target at the time of coupling showed, as a result of the simulation, the compound with the highest bioaffinity value, Hit 998, with the energy of −17.62 kcal/mol, and synthetic viability close to 50%. While hit 1103 presented better synthetic viability (80%), its affinity energy of −10.28 kcal/mol. Both were compared with the reference linker N3, with a binding affinity of −7.5 kcal/mol. ADMET tests demonstrated that simulated compounds have a low risk of metabolic activation and do not exert effective distribution in the CNS, suggesting a pharmacokinetic mechanism based on local action, even with high topological polarity, which resulted in low oral bioavailability. In conclusion, MMGBSA, H-bonds, RMSD, SASA, and RMSF values were also obtained through molecular dynamics to verify the stability of the receptor-ligant complex within the active protein site to seek new therapeutic propositions in the fight against the pandemic. Communicated by Ramaswamy H. Sarma